Frequency of Desaturation and Association With Hemodynamic Adverse Events During Tracheal Intubations in PICUs. Issue 1 (January 2018) - Li, Simon; Hsieh, Ting-Chang; Rehder, Kyle J.; Nett, Sholeen; Kamat, Pradip; Napolitano, Natalie; Turner, David A.; Adu-Darko, Michelle; Jarvis, J. Dean; Krawiec, Conrad; Derbyshire, Ashley T.; Meyer, Keith; et al.
Abstract : Objectives: Oxygen desaturation during tracheal intubation is known to be associated with adverse ICU outcomes in critically ill children. We aimed to determine the occurrence and severity of desaturation during tracheal intubations and the association with adverse hemodynamic tracheal intubation–associated events. Design: Retrospective cohort study as a part of the National Emergency Airway Registry for Children Network's quality improvement project from January 2012 to December 2014. Setting: International PICUs. Patients: Critically ill children younger than 18 years undergoing primary tracheal intubations in the ICUs. Interventions: tracheal intubation processes of care and outcomes were prospectively collected using standardized operational definitions. We defined moderate desaturation as oxygen saturation less than 80% and severe desaturation as oxygen saturation less than 70% during tracheal intubation procedures in children with initial oxygen saturation greater than 90% after preoxygenation. Adverse hemodynamic tracheal intubation–associated event was defined as cardiac arrests, hypo or hypertension requiring intervention, and dysrhythmia. Measurements and Main Results: A total of 5, 498 primary tracheal intubations from 31 ICUs were reported. Moderate desaturation was observed in 19.3% associated with adverse hemodynamic tracheal intubation–associated events (9.8% among children with moderate desaturation vs 4.4% without desaturation; p < 0.001). Severe desaturation was observed in 12.9% of tracheal intubations, also significantly associated with hemodynamic tracheal intubation–associated events. After adjusting for patient, provider, and practice factors, the occurrence of moderate desaturation was independently associated with hemodynamic tracheal intubation–associated events: adjusted odds ratio 1.83 (95% CI, 1.34–2.51; p < 0.001). The occurrence of severe desaturation was also independently associated with hemodynamic tracheal intubation–associated events: adjusted odds ratio 2.16 (95% CI, 1.54–3.04; p < 0.001). Number of tracheal intubation attempts was also significantly associated with the frequency of moderate and severe desaturations ( p < 0.001). Conclusions: In this large tracheal intubation quality improvement database, we found moderate and severe desaturation are reported among 19% and 13% of all tracheal intubation encounters. Moderate and severe desaturations were independently associated with the occurrence of adverse hemodynamic events. Future quality improvement interventions may focus to reduce desaturation events. Abstract : Supplemental Digital Content is available in the text.